Partizanska zgodba v sodobnem slovenskem romanu - Zupan Sosič, Alojzija (Jezik in slovstvo, 2014)
In the new millennium, the Partisan story has become very common in the contemporary Slovenian novel. As in the current social situation, the genre establishes different relationships towards the Partisan struggle for freedom in the following novels: Da me je strah? by Maruša Krese, Saga o kovčku by Nedeljka Pirjevec, Angel pozabe (Engel des Vergessens) by Maja Haderlap, Opoldne zaplešejo škornji by Zdenko Kodrič, Paloma negra by Miha Mazzini, Ubijanje kače by Jože Snoj and To noč sem jo videl by Drago Jančar. The relationships oscillate between ethical responsibility and historical memory through a reassessment of history to the point of relativising it in the sense of the demythologisation, profanation, exotification and poeticisation of the Partisan struggle.
Keywords: Slovene literature; slovenska književnost; slovenska proza; sodobni slovenski roman; partizanska zgodba; relativizacija zgodbe; zgodovinski spomin